Ecopark Berbasis Keberlanjutan pada Hutan Albasia di Desa Kuala Dua Kabupaten Kubu Raya - Andhika Putra Noer Virgiawan; Muhammad Hidayat; Caesar Destria (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
The decline in the environmental quality of tourism locations in the development and management system is one of the main factors that make tourist destinations no longer attractive to the public. This study aims to design a transition from a forest tourism that is experiencing environmental degradation to an Ecopark through a tourism and sustainability concept. This way, the current environmental content can have alternative solutions. The implementation of the research in this case uses several methods including case studies, surveys, data processing, analysis, spatial program analysis and concepts in the form of design visualization. The research location is in the Albasia Forest in Kuala Dua Village, Kubu Raya Regency, which is a productive forest from an industry that was converted into a village tourism location. This study focuses on an environmental issue that is raised in order to encourage aspects of sustainability in the Albasia Forest itself and its surrounding environment. The conclusion of this design is to create a public space with an Ecopark basis as an effort to restore the identity of a public tourism space that is oriented towards improving the environment to activity spaces and can be a reference for local governments or local figures for subsequent designs.